A MODELLING APPROACH TO UNDERSTAND CHARGE DISCHARGE DIFFERENCES IN THERMAL BEHAVIOUR IN LITHIUM IRON PHOSPHATE – GRAPHITE BATTERY. (20th July 2017) - Maheshwari, Arpit; Dumitrescu, Mihaela Aneta; Destro, Matteo; Santarelli, Massimo
Highlights: Parameterization of an electrochemical – thermal model for charge. Validation from 0.1C to 10C without considering phase change in LiFePO4 electrode. Hysteresis and different particle radius inclusion in charge model are sufficient. Higher temperature during charge due to more reversible heat production. Heat production in the porous graphite electrode is found to be dominant Abstract: Lithium iron phosphate is a promising positive electrode material. It shows apparent asymmetry between charge and discharge affecting not only the electrochemical but also the thermal behaviour. Physics based models for batteries are usually parameterized for discharge behaviour, which can lead to inaccuracies in prediction of battery behaviour during charging or dynamic conditions, especially in the case of this battery chemistry. This has consequences for battery modelling and safety. A pseudo 2D electrochemical – 3D thermal model is parameterized for charging using experimental data. Substantial differences in parameters between charge and discharge are seen in the validated model. The model is used to quantify the thermal differences during charging and discharging and separate the contribution of the different battery layers. Reversible heat losses are seen to be the main cause for the difference between charge and discharge while graphite electrode are seen to have a much higher heat contribution compared to lithium iron phosphate electrode.